Silicon negative electrode material with porous coating layer and preparation method thereof
By covering the conductive carbon layer and porous fast ion conductor layer on the surface of the silicon negative electrode material, the problem of poor electronic conductivity and ionic conductivity of silicon oxide materials in lithium batteries is solved, and efficient conductivity and buffer volume expansion are achieved , extends the cycle life of the material and improves fast charging performance.
Patent Information
- Application Number
- CN202011602658.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-30
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-12-30
AI Technical Summary
Silicon oxide materials have poor electronic conductivity and ionic conductivity in lithium batteries, and have a large volume expansion effect, which affects its chemical properties.
The silicon negative electrode material using a porous cladding layer is used to coat the conductive carbon layer and the porous fast ion conductor layer on the surface of the silicon-based material to improve the electronic conductivity and ionic conductivity of the material and buffer volume expansion.
The high electronic and ionic conductivity of the material is achieved, which extends the cycle life of the material and improves the fast charging performance.
Smart Images

Figure CN114695847B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a silicon negative electrode material with a porous coating layer and a preparation method thereof. Background Art
[0002] As lithium batteries are increasingly used in portable electronic 3C devices, electric vehicles, logistics, ships, aviation and other fields, people's requirements for their high energy density and high rate characteristics are becoming more and more clear. The negative electrode material is a key factor in determining the characteristics of lithium batteries, and silicon materials, as negative electrode materials with high specific capacity, have become a research boom among scholars in recent years. At present, silicon negative electrode materials mainly include silicon element, silicon-carbon materials, silicon oxide materials, silicon alloys, silicon nanowires, etc. Among them, silicon oxide is more widely studied due to its relatively small volume effect, low operating voltage and good safety. However, the poor electronic conductivity and ionic conductivity of silicon oxide materials and the earth's influence affect the performance of their chemical properties. Therefore, how to improve the electronic conductivity and ionic conductivity of the material and how to further reduce the volume expansion effect are key technical issues for the practical application of this material. Summary of the invention
[0003] In response to the above problems, the present application provides a silicon negative electrode material with a porous coating layer, which can effectively improve the electronic conductivity of the silicon oxide material while improving the ionic conductivity, thereby making it possible to use the material in fast-charging batteries.
[0004] In one embodiment, the present application provides a silicon negative electrode material with a porous coating layer, including a silicon-based material, a conductive carbon layer and a fast ion conductor layer, wherein the conductive carbon layer is coated on the surface of the silicon-based material, and the fast ion conductor layer is coated on the surface of the conductive carbon layer; the fast ion conductor layer is a porous structure.
[0005] In one embodiment, the present application also provides a method for preparing the above silicon negative electrode material, comprising the following steps:
[0006] (1) SiO 2 The powder and Si powder are mixed evenly in a certain proportion and placed in a vacuum furnace. The temperature in the furnace is maintained at 900~1300℃ and the pressure is maintained at 0~5000Pa. The evaporated product is cooled into blocks and then crushed and sieved to obtain SiO x powder;
[0007] (2) Place SiO powder in a chemical vapor deposition (CVD) furnace, maintain the furnace temperature at 600-1100°C and the gas pressure at 0-5000 Pa, introduce carbon source gas into the furnace, and deposit for 1-5 hours to deposit cracked carbon on the SiO x Surface, complete carbon coating, obtain SiO x / C composite powder;
[0008] (3) SiO x The SiO2 / C composite powder is mixed evenly with a certain proportion of lithium source and / or magnesium powder, and heated to 500-1000°C in a high-temperature furnace while introducing argon gas for protection to obtain lithium-doped and / or magnesium-doped SiO2 x / C composite powder.
[0009] (4) The composite powder obtained in step (3) is mixed with the fast ion conductor powder, uniformly dispersed in pure water, and a certain proportion of a foaming agent is added to obtain a mixed solution with a large number of tiny bubbles. The mixture is then spray dried, and bubbles are broken to form pores during the powder drying process, thereby obtaining a silicon negative electrode material coated with a porous fast ion conductor layer.
[0010] Beneficial effects of the present application: The silicon negative electrode material provided by the present application has a double-layer coated core-shell structure, wherein silicon oxide is used as the core to ensure high specific capacity and low volume change, a conductive carbon layer is used as the first coating layer to improve the electronic conductivity of the material, and a fast ion conductor layer is used as the second coating layer to improve the ion conductivity of the material. At the same time, the fast ion conductor layer is a porous structure, and pores with a certain pore size will expose the conductive carbon layer, avoiding the problem of the coating of the fast ion conductor layer reducing the electronic conductivity, and the porous structure can further buffer the volume expansion of the silicon material during the charging and discharging process, so that the material has a longer cycle life and better fast charging performance.
[0011] Additional aspects and advantages of the embodiments of the present application will be described and shown in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic diagram of the principle of testing the coverage of the fast ion conductor layer using the XPS method of the present invention;
[0013] Figure 2 This is a SEM image of the silicon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0014] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0015] In this application, amounts, ratios, and other numerical values are presented in a range format, and it should be understood that such range format is used for convenience and brevity and should be flexibly interpreted to include not only the values explicitly specified as range limits, but also all individual values or sub-ranges encompassed within the range, as if each value and sub-range were explicitly specified.
[0016] In the application, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. Item A may include a single element or multiple elements, and item B may include a single element or multiple elements.
[0017] In this application, a list of items connected by the term "and / or" or other similar terms may mean any combination of the listed items. For example, if items C and D are listed, the phrase "C and / or D" means only C; only D; or C and D. Item C may include a single element or multiple elements, and item D may include a single element or multiple elements.
[0018] In this application, D50 is the particle size corresponding to when the cumulative volume percentage of the material reaches 50%.
[0019] This embodiment provides a silicon negative electrode material with a porous coating layer, including a silicon-based material, a conductive carbon layer and a fast ion conductor layer, wherein the conductive carbon layer is coated on the surface of the silicon-based material, and the fast ion conductor layer is coated on the surface of the conductive carbon layer; the fast ion conductor layer is a porous structure. The silicon-based material can ensure the high specific energy characteristics of the battery, the double-layer coating of the conductive carbon layer and the porous fast ion conductor layer can simultaneously improve the electronic conductivity and ionic conductivity, and the fast ion conductor layer can further buffer the volume expansion.
[0020] In some embodiments, based on the total mass of the silicon negative electrode material as 100%, the mass proportion of the fast ion conductor layer is 0.1wt%~10wt%, preferably 0.3~5wt%. If the mass ratio is less than 0.1wt%, the increase in ionic conductivity is not obvious. If the mass is greater than 10wt%, the specific capacity of the material will be reduced. The thickness of the fast ion conductor layer is 1~20nm, preferably 3~10nm. If the thickness is less than 1nm, the increase in ionic conductivity is not obvious. If the thickness is greater than 10nm, the electronic conductivity of the material will be seriously affected.
[0021] In some embodiments, the general chemical formula of the silicon-based material is SiOx, wherein 0<x<2; the particle size of the silicon-based material is D50=1~20μm; the silicon-based material also includes at least one of a lithium compound and a metal magnesium salt, and the doping of Li and Mg metal elements can improve the first coulombic efficiency of the silicon material.
[0022] In some embodiments, the coverage of the fast ion conductor layer is 10-90%, preferably 50-70%. If the coverage is greater than 90%, there are too few pores, the conductivity of the material deteriorates, which is not conducive to electronic conductivity, and the fast charging performance of the material decreases; if the coverage is less than 10%, it affects the ion conductivity, and the fast ion conductor layer has too many pores, the structural strength deteriorates, and the silicon-based core expansion cannot be effectively alleviated, and the material cycle life decreases. The coverage can be calculated by XPS (X-ray photoelectron spectroscopy analysis) test, and the specific test method is as follows: There are three states on the surface of the silicon negative electrode material, one is the physical position of the fast ion conductor layer, the second is the pore position of the exposed carbon layer, and the third is the pore position of the exposed silicon-based material core. When using XPS testing, such as Figure 1 As shown, X-rays are irradiated to the surface of the negative electrode material, and the pore position of the exposed carbon layer returns the signal of the C element, and the percentage content c of the C element is calculated; the pore position of the exposed silicon-based core returns the signal of the Si and O elements, and the percentage content y of the Si element is calculated. Since Si:O=1:x in the silicon-based core, the percentage content of the O element at the pore position is x*y; the physical position of the fast ion conductor is the difference between the total surface area of the negative electrode material and the pore position, and its ratio to the surface area of the negative electrode material is the coverage A of the fast ion conductor layer, and the coverage A is calculated by formula (I):
[0023] (I)
[0024] Where A represents the coverage, c represents the percentage of C atoms measured by XPS, y represents the percentage of Si atoms, and x represents the percentage of SiO x The value of x in the general formula.
[0025] In some embodiments, the silicon-based material contains dispersed silicon microcrystals, and from the X-ray diffraction pattern analysis, the half-width of the diffraction peak belonging to Si (111) in the range of 2θ=28~28.8° is greater than 2.7°, and the corresponding silicon microcrystal size is less than 3nm. At this time, the silicon microcrystals are more similar to amorphous silicon, and amorphous silicon is isotropic, has uniform volume expansion, is not easy to pulverize, produces new surface, consumes more electrolyte, and thus exhibits better cycle performance.
[0026] In some embodiments, the conductive carbon of the conductive carbon layer is at least one of hard carbon, soft carbon, carbon black, graphite, and carbon fiber; and the thickness of the conductive carbon layer is 2 to 300 nm.
[0027] In some embodiments, the fast ion conductor of the fast ion conductor layer is any material having SEI membrane function, including but not limited to at least one of lithium fluoride, lithium phosphate, lithium metaphosphate, lithium aluminum phosphate, aluminum phosphate, aluminum metaphosphate, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, lithium hydroxide, lithium carbonate, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, LiPON, LLZO, LATP, LLTO, PEO and its derivatives complex lithium salt polymer electrolytes, CMC, CMC-Li, PAA, PAA-Li, PAN, PAN-Li, epoxy resin, phenolic resin, and urea-formaldehyde resin.
[0028] This embodiment also provides a method for preparing the above silicon negative electrode material, comprising the following steps:
[0029] (1) SiO 2 The powder and Si powder are mixed evenly in a certain proportion and placed in a vacuum furnace. The temperature in the furnace is maintained at 900~1300℃ and the pressure is maintained at 0~5000Pa. The evaporated product is cooled into blocks and then crushed and sieved to obtain SiO x The certain ratio is preferably 0.3-4:1, more preferably 0.6-1.5:1; the crushing is to crush the material by at least one of ball milling, sand milling, air flow milling, mechanical milling and the like; the screening is to screen out particles of suitable particle size by air flow mill classification, vibrating screen and the like.
[0030] (2) SiO x The powder is placed in a chemical vapor deposition (CVD) furnace, the temperature in the furnace is maintained at 600~1100℃, the pressure is maintained at 0~5000Pa, and the carbon source gas is introduced into the furnace for 1~5h to deposit the cracked carbon on the SiO x Surface, complete carbon coating, obtain SiO x / C composite powder; the carbon source gas is hydrocarbon C y H z (y≤4), including but not limited to a mixture of one or more of methane, ethane, ethylene, acetylene, propane, propylene and butane.
[0031] (3) SiO x The SiO2 / C composite powder is mixed evenly with a certain proportion of lithium source and / or magnesium powder, and heated to 500-1000°C in a high-temperature furnace while introducing argon gas for protection to obtain lithium-doped and / or magnesium-doped SiO2 x / C composite powder; the lithium source is not specifically limited, and is preferably at least one of metallic lithium, lithium nitride, and lithium hydride; the certain proportion is preferably 5~30wt%.
[0032] (4) The composite powder obtained in step (3) is mixed with the fast ion conductor powder, and the mixture is evenly dispersed in pure water. A certain proportion of a foaming agent is then added to obtain a mixed solution having a large amount of tiny bubbles, and the mixture is spray dried. During the drying process of the powder, the bubbles burst to form pores, and a silicon negative electrode material coated with a porous fast ion conductor layer is obtained. The certain proportion is preferably 0.01-0.1 wt % based on the total mass of the composite powder as 100%. The foaming agent can be selected from at least one of calcium carbonate, magnesium carbonate, and sodium bicarbonate. The process conditions for spray drying are not specifically limited. Preferably, the air inlet temperature is 180-250° C., the air outlet temperature is 100-110° C., and the spray pressure is 0.1-1.0 MPa.
[0033] Example 1
[0034] SiO 2 The powder and Si powder were mixed evenly in a mass ratio of 1:1 and placed in a vacuum furnace, heated to 1100°C, and the gas pressure was maintained at 100 Pa. The evaporation product was cooled into blocks and then crushed and sieved to obtain SiO (x=1) powder with a diameter D50=5μm.
[0035] The SiO powder obtained in the previous step was heated to 950°C in a chemical vapor deposition (CVD) furnace, the vacuum degree in the furnace was controlled at 300 Pa, and methane with a flow rate of 9 L / min and argon with a flow rate of 18 L / min were introduced for a deposition time of 1 hour. Methane was cracked at high temperature, and pyrolytic carbon was coated on the SiO surface, and the thickness of the carbon coating layer was 10 nm.
[0036] SiO / C composite powder was mixed with 1.5wt% LiPO 3 Mix, add pure water and stir evenly, then add 0.1wt% calcium carbonate foaming agent, continue to stir evenly and spray dry, during the powder drying process, bubbles burst to form pores, and a silicon negative electrode material coated with a porous fast ion conductor layer is obtained. Among them, LiPO 3 The thickness of the coating layer is 5 nm.
[0037] Figure 2 This is a SEM image of the silicon negative electrode material prepared in Example 1. It can be seen that the fast ion conductor layer on the surface of the prepared silicon negative electrode material has a microporous structure.
[0038] 1 g of the obtained silicon negative electrode material was sampled, washed with anhydrous ethanol, and dried at 105°C to obtain the sample to be tested. The Thermo Fisher Escalab 250 Xi photoelectron spectrometer was used to perform narrow spectrum scanning on the C and Si elements in the sample to be tested. After fitting the test results, the narrow spectrum scanning peak area of the above elements was obtained, and the atomic number percentage a of each element in the sample was calculated according to formula (II):
[0039] (II)
[0040] Among them, a represents the percentage of the number of atoms of each element, n represents the atomic concentration, and S represents the sensitivity factor.
[0041] The calculation results are shown in Table 1. The calculated coverage A of the fast ion conductor layer is: 100%-27.6%-1.2%-1.2%*1=70.0%.
[0042] Table 1 Atomic number percentage of elements on the surface of powder samples of Example 1
[0043] Name Atomic % C 27.6 Si 1.2
[0044] The electronic conductivity is tested by the following method: the four-wire two-terminal method is used to determine the resistance by measuring the voltage across the two ends of the resistor to be tested and the current flowing through it, and the conductivity is calculated by combining the height and bottom area of the resistor to be tested. A certain amount of powder is added to the test mold, and after gently shaking it flat, the gasket on the mold is placed on the sample; after the sample is loaded, the mold is placed on the workbench of the electronic pressure testing machine, and the pressure is increased to 500kg (159Mpa) at a rate of 5mm / min, constant pressure is maintained for 60s, and then the pressure is released to 0; when the sample is constant pressured to 5000±2kg (about 15 to 25s after the pressure is increased to 1 to 5000kg), the sample pressure is recorded, and the sample deformation height is read, and the value displayed by the resistance tester at this time is recorded, and the electronic conductivity can be calculated using formula (III):
[0045] (III)
[0046] Among them, C represents electronic conductivity, ρ represents resistivity, S represents bottom area, and R represents resistance.
[0047] The silicon negative electrode material prepared in Example 1 above was assembled into a button-type lithium battery, and its electrochemical performance was tested.
[0048] The button lithium battery was assembled in the following manner: the prepared silicon negative electrode material powder was mixed with the graphite negative electrode (mass ratio 20:80) to obtain a mixed negative electrode powder, and then the mixed negative electrode powder, SP, CNT, CMC (sodium carboxymethyl cellulose), and SBR (styrene butadiene rubber) were mixed at a mass ratio of 95.2:0.85:0.15:1.2:2.6, and stirred continuously for 8 hours with a magnetic stirrer until it became a paste. The stirred slurry was poured on a copper foil with a thickness of 9μm, coated with an experimental coater, and dried at 85℃ under vacuum (-0.1MPa) for 6 hours to obtain a negative electrode sheet. Then, NCM811 positive electrode material, SP, CNT, and PVDF (polyvinylidene fluoride) were mixed at a mass ratio of 90:2:1:7, and an appropriate amount of NMP (N-methylpyrrolidone) was added as a solvent, and stirred continuously for 8 hours with a magnetic stirrer until it became a paste. The stirred slurry was poured onto an aluminum foil with a thickness of 16 μm, coated with an experimental coating machine, and dried at 85 °C under vacuum (-0.1 MPa) for 6 h to obtain a positive electrode sheet. The positive and negative electrode sheets were rolled to 100 μm on a manual roller machine, and then a 12 mm diameter disc was obtained using a punching machine. It was dried at 85 °C under vacuum (-0.1 MPa) for 8 h, weighed, and the weight of the active material was calculated. A CR2032 button-type full battery was assembled in a glove box, using a polypropylene microporous membrane as the separator and 1 mol / L LiPF 6 in EC:DEC=1:1Vol% with 5.0%FEC as electrolyte.
[0049] The following method was used to test the lithium ion conductivity: the button cell was charged and discharged using the LAND battery test system. After standing for 6 hours, it was discharged at 0.05C to 0.005V, and then discharged at 0.01C to 0.005V; after standing for 5 minutes, it was charged to 1.5V at 0.05C constant current; after standing for 5 minutes, the above steps were repeated twice, and then the button cell was tested for electrochemical impedance spectroscopy using an electrochemical workstation. The frequency range is 0.01~10 5 Hz, the voltage amplitude is 0.005V, and the last 5 data points are taken to obtain the linear slope of Z' to the rotation speed w^-0.5 at low frequency. The slope value is the Warburg parameter. Under the same test conditions, the smaller the Warburg parameter, the higher the lithium ion conductivity.
[0050] The cycle performance was evaluated in the following manner: the button-type full battery was left at room temperature for 12 hours, and then subjected to constant current charge and discharge test on a blue power test system, with charge and discharge at a current of 0.25C and a charge and discharge cut-off voltage of 3.0-4.25V. The capacity retention rate was calculated by dividing the discharge capacity of the 100th cycle by the discharge capacity of the 1st cycle × 100%, and the higher the value, the better the cycle performance.
[0051] The rate performance was evaluated in the following way: the button-type full battery was left to stand at room temperature for 12 hours, and then the constant current charge and discharge test was performed on the Blue Electric test system, with a charge and discharge cut-off voltage of 3.0~4.25V. The battery was first charged and discharged at a current of 0.25C for 3 cycles. Then, the battery was charged and discharged at a current of 0.5C for 3 cycles. Finally, the battery was charged and discharged at a current of 1C for 3 cycles. The capacity retention rate was calculated by dividing the discharge capacity of the 9th cycle by the discharge capacity of the 1st cycle by 100%. The higher the value, the better the rate performance.
[0052] Embodiment 2-6
[0053] The other steps and process parameters are the same as those in Example 1, except that the thickness of the fast ion conductor coating layer is changed by controlling the amount of fast ion conductor powder added, and the coverage of the fast ion conductor coating layer is controlled by the amount of foaming agent added. In addition, the powder is tested and the secondary battery is evaluated in the same manner as in Example 1.
[0054] Comparative Example 1
[0055] The other steps and process parameters are the same as those in Example 1, except that no foaming agent is added, and the fast ion conductor coating layer does not form a porous structure;
[0056] In addition, the powder was tested and the secondary battery was evaluated in the same manner as in Example 1.
[0057] Table 2 shows the test results of various embodiments and comparative examples. The test results of various embodiments and comparative example 1 show that the porous LiPO 3 The silicon negative electrode material of the coating layer has high electronic conductivity and ionic conductivity, and thus has excellent capacity retention and rate performance; the test results of each embodiment show that by controlling the coverage and thickness of the fast ion conductor, a silicon negative electrode material with the best cycle and rate performance can be obtained.
[0058] Table 2 Test results of various embodiments and comparative examples
[0059]
[0060] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the above description is not a limitation of the invention, and the present invention is not limited to the specific embodiments disclosed and described above. Some modifications and changes to the invention, such as changes, modifications, additions or substitutions made by those skilled in the art within the essential scope of the embodiments to the equivalent replacement of each raw material and the addition of auxiliary components, the selection of specific methods, etc., should also fall within the scope of protection of the claims of the present invention.
Claims
1. A silicon negative electrode material with a porous coating layer, comprising a silicon-based material, a conductive carbon layer and a fast ion conductor layer, characterized in that: The conductive carbon layer is coated on the surface of the silicon-based material, and the fast ion conductor layer is coated on the surface of the conductive carbon layer; the fast ion conductor layer is a porous structure; the chemical general formula of the silicon-based material is SiO x , where 0 < x < 2, the particle size of the silicon-based material is D50 = 1 to 20 μm; the fast ion conductor material of the fast ion conductor layer includes at least one of lithium fluoride, lithium phosphate, lithium metaphosphate, lithium aluminum phosphate, aluminum phosphate, aluminum metaphosphate, aluminum oxide, magnesium oxide, zinc oxide, titanium oxide, zirconium oxide, lithium hydroxide, lithium carbonate, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, LiPON, LLZO, LATP, LLTO; The method for preparing the silicon negative electrode material comprises the following steps: (1) SiO2 powder and Si powder are mixed evenly in a certain proportion and placed in a vacuum furnace. The temperature in the furnace is maintained at 900~1300℃ and the pressure is maintained at 0~5000Pa. The evaporated product is cooled into blocks and then crushed and sieved to obtain SiO x powder; (2) SiO x The powder is placed in a chemical vapor deposition (CVD) furnace, the temperature in the furnace is maintained at 600~1100℃, the pressure is maintained at 0~5000Pa, and the carbon source gas is introduced into the furnace according to the required proportion for 1~5h to deposit the cracked carbon on the SiO x Surface, complete carbon coating, obtain SiO x / C composite powder; (3) SiO x The SiO2 / C composite powder is uniformly mixed with a certain proportion of lithium source and / or magnesium powder, and heated to 500-1000°C in a high-temperature furnace while introducing argon gas for protection to obtain lithium-doped and / or magnesium-doped SiO2 x / C composite powder; (4) The composite powder obtained in step (3) is mixed with the fast ion conductor powder, uniformly dispersed in pure water, and then a certain proportion of a foaming agent is added to obtain a mixed solution with a large number of tiny bubbles, which is then spray-dried. During the powder drying process, the bubbles burst to form pores, thereby obtaining a silicon negative electrode material coated with a porous fast ion conductor layer and a conductive carbon layer.
2. The silicon negative electrode material according to claim 1, characterized in that Taking the total mass of the silicon negative electrode material as 100%, the mass proportion of the fast ion conductor layer is 0.1wt%~10wt%; the thickness of the fast ion conductor layer is 1~20nm.
3. The silicon negative electrode material according to claim 1, characterized in that: The coverage rate of the fast ion conductor layer is 10-90%.
4. The silicon negative electrode material according to claim 1, characterized in that: The silicon-based material contains dispersed silicon microcrystals, and according to an X-ray diffraction spectrum analysis, the half-width of the diffraction peak belonging to Si (111) in the range of 2θ=28-28.8° is greater than 2.7°, and the corresponding silicon microcrystal size is less than 3nm.
5. The silicon negative electrode material according to claim 1, characterized in that: The thickness of the conductive carbon layer is 2-300 nm.
Citation Information
Patent Citations
Silicon dioxide composite anode material for lithium ion battery, as well as preparation method and application of silicon dioxide composite anode material
CN104022257A
Double covered silicon-based composite materialSi@C@TiO2 and preparation method thereof
CN106099062A
Preparation method of silicon-carbon negative electrode material with characteristics of high primary effect and long service life
CN108336312A
Lithium battery negative electrode material and preparation method thereof
CN111244410A